Hegemony and Music in The Pre-Colonial, Colonial and Post-Colonial Zimbabwe - Matiure, Perminus (Association of Ethnomusicology, 2022)
The article is an expose' of how hegemony and music belonging to the Shona communities of Zimbabwe have transcended the pre-colonial, colo- nial and post-colonial periods. The discussion is premised on some onto- logical comprehension that supremacy, socio-economic and political do- minance by members of a community are aspects of power dynamics and hegemony. As such the world communities are characterized by class struggle in which the 'haves', who enjoy hegemony superimpose on the 'have-nots'. Communities are in a dilemma of trying to reduce the gap between the ‘haves’ and ‘have-nots’. In this study, a qualitative ethnograp- hic methodology was carried out among some Shona communities of Zim- babwe. The findings were that music portrays socio-economic and political hegemonies during the pre-colonial, colonial and post-colonial Zimbabwe. It was also established that there is a strong relationship between music and hegemony. Music, especially song and dance were used to achieve socio- economic and political dominance during the three eras